The effect of worked examples and extra help on math anxiety and equation learning in French-speaking Belgium - JACMART, Sara; Dragone, Laetitia; Temperman, Gaëtan; Lièvre, Bruno De (American Journal of Education and Learning, 2025)
This study examined the effectiveness of worked examples as a teaching strategy to improve students' performance in mathematics and to reduce their level of anxiety. This instructional approach was implemented during a mathematics course to teach equation solving to 47 students in the second year of secondary school in French-speaking Belgium, where both high levels of mathematics anxiety and low performance in equation solving had been observed. The study also explored the impact of adding extra support that detailed each step of the worked examples on these two variables. Only one of the two groups was given the opportunity to access these additional explanations through QR codes. Pre- and post-experimental observations were conducted in order to assess the effect of this practice on both variables. The results showed that worked examples, whether accompanied by additional help or not, had a significant positive effect on students’ mathematical performance. However, no significant effect on mathematics-related anxiety was observed in either group. Moreover, the addition of extra support did not result in any significant difference in terms of reducing anxiety or improving performance when compared to the use of worked examples alone. Thus, the study confirms that worked examples can efficiently support equation solving even without the addition of extra help.